PRESENTING AN INTERACTIVE MARKETING MODEL WITH A CUSTOMER KNOWLEDGE MANAGEMENT APPROACH IN THE TOURISM INDUSTRY - Dr. Ali Abbood Awdaa; Ali Fadhil Al yuosife; Suadad Ali Abed Alabbas (Scholars Digest Publishing, 2024)
This research aims to present an interactive marketing model that integrates the customer knowledge management approach in the tourism industry, taking into account the causal, contextual and intervening variables affecting this sector. Using interview tools with experts and senior managers in the tourism industry, 98 factors related to interactive marketing and customer knowledge management were identified. The structures associated with each variable were formulated using open, central and selective coding methods. The data extracted from the research questionnaire were analyzed, The results showed that the factor loading of the research variables was higher than 0.4, and the pooled reliability was higher than 0.7, which enhances the validity of the theoretical structure of the factors, strategies and implications of the research model. Through the structural equations method and estimation of the final model, the role of causal and contextual factors, customer knowledge management strategy and intervening factors in influencing interactive marketing was confirmed. These factors were ranked in terms of influence in the first four places in the final research model. Finally, the research model with the best overall fit is presented, and it is recommended to focus on its impacts and implications, including: enhancing the internal performance of tourism enterprises, achieving competitive advantage, improving customer experience and brand management, and enhancing customer satisfaction and market results.